TURKEY AND SECURITY IN THE SOUTHERN CAUCASUS: THE CAUCASUS STABILITY AND COOPERATION PLATFORM - MANCHKHASHVILI, Maya (CENTRAL ASIA AND THE CAUCASUS, 2010)
The August 2008 war between Russia and Georgia tipped the balance of forces in the Southern Caucasus and made it harder to set up a regional security system.The new challenges (occupation of Georgia’s two regions and recognition of their independence) were set off by certain positive shifts (the “football diplomacy” between Turkey and Armenia and the Zurich Protocols) which, however, did not carry enough weight to accelerate the peacekeeping process.The Caucasus Stability and Cooperation Platform Turkey laid on the table in the wake of the August war obviously had no future, although it clarified the problems to a certain extent and inspired the quest for new and more adequate decisions.